The muted ones: a study miscommunication and Isolation in Tennessee Williams’ Cat on a Hot Tin Roof - AlHasan, Hussein Kanosh (International Journal of Psychosocial Rehabilitation, 2020)
The truth behind communication which uncover the hidden veil of incomprehension and internal fractions is one of the highlighted metaphor in Thomas Lanier Williams III literary play Cat on a hot Tin Roof (1955) as the characters seems to suffer in exposing their reality and undressing their personality to one another. This study will be textually limited to T.L. Williams’ Cat on a Hot Tin Roof (1955), the analysis will be limited to the three key characters Margaret, Brick and Big Daddy as they reveal their lack of the basic elements of communication. Theoretically, this study will be limited to the notion of communication and possible causes of miscommunication. This study will examine the main characters in the selected play to establish their scene of communication. Moreover, this study will investigate the factors which cause the lack of communication in the selected literary play. Finally, this study will highlight the types of communicative relationships which the main characters seem to be sharing. Bricks as the protagonist of the play present the ideal example of the external and internal struggles as he displays the hardship of relationships and communicating with others even family.